Pengaruh Pendidikan Kesehatan Kanker Payudara Terhadap Pengetahuan, Perilaku dan Keterampilan Sadari pada Wanita Usia Subur yang Berkunjung ke Pmb Utami Dewi di Cihideung Bogor Tahun 2023 - Yasmin Raihanny; Kuswati Kuswati; Agustina Sari (Student Research Journal, 2024)
. Health education is to change the knowledge, attitudes and skills of individuals or community groups in the health sector, promote and maintain healthy lifestyles, and be active in achieving optimal health. The aim of this research is to see the effect of breast cancer health education on knowledge, behavior and BSE skills in women of childbearing age who visit PMB Utami Dewi in Cihideung Bogor in 2023. This research method is to use a Quasi Experiment with a one group pretest posttest research design. So the sample in this study amounted to 30 respondents. This research instrument uses a questionnaire containing knowledge, behavior and skills regarding BSE. Based on the results of the paired sample t test, it shows a significance value of 0.000, so it can be concluded that breast cancer health education influences knowledge, behavior and awareness skills in women of childbearing age who visit Pmb Utami Dewi in Cihideung Bogor in 2023.